Pengaruh Budaya Organisasi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Di Sekolah Menengah Kejuruan Bina Mandiri Bogor - Rizki Ananda Febriani Nazwar; Muhamad Aziz Firdaus; Hannisa Rahmaniar Hasnin (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research examines the influence of organizational culture and work environment on the employees performance. The data used in this research was obtained from employees of Sekolah Menengah Kejuruan Bina Mandiri Bogor. Quantitative research method used in this research, survey held by questionnaires to 35 employees at Sekolah Menengah Kejuruan Bina Mandri Bogor. This research uses multiple linear regression analysis to test the relationship between independent variables, namely organizational culture and work environment, with the dependent variable, namely employee performance. The sample in this study consisted of 35 respondents. The work environment variable . For the Work Environment variable Sekolah Menengah Kejuruan Bina Mandiri Bogor. Based on research results with F test results with a value of 148,769 > 3,295, it shows that there is a simultaneous influence with positive and significant results between the variables Organizational Culture (X1) and Work Environment (X2) on the Performance (Y) of Sekolah Menengah Kejuruan Bina Mandiri Bogor.